Assessment of endothelial dysfunction by flow mediated dilatation in patients with Coronary Artery Disease - Salih, Saba F.; Mohammed, Najeeb H.; Muslim, Abbas N.; Al-Misebawi, Sarab H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Endothelial dysfunction is thought to be a key event in the development of atherosclerosis. It is a systemic process that simultaneously affects different vascular territories including coronary arteries. It is recommended that noninvasive approaches assessing endothelial function in peripheral vessels like flow mediated dilatation are indirectly representative of coronary vascular function. Objectives: This study is aimed to assess endothelial dysfunction by using flow mediated dilatation in patients with coronary artery disease Patients and methods: 82 patients of either sex with an age range of 40-65years are involved in this study. Each patient was subjected to two tests; first test was the flow mediated dilatation percentage (FMD%) measurement to assess endothelial functional integrity and second one was coronary computerized tomography angiography for measuring the percentage of coronary artery stenosis. Results: the results of this study revealed that FMD% is inversely correlated with the percentage of coronary artery stenosis (p value <0.01). FMD% in patients having a single coronary vessel atheromatous stenosis (9.9±3.5) % was significantly lower than that of control subjects (15.3±7) %, p<0.0001. Conclusion: this study concludes that FMD% of brachial artery could be used as a marker for systemic endothelial functional integrity including that of coronary arteries.